(untitled) (Clinics, 2013)
OBJECTIVE: This prospective study investigated the diagnostic significance of the N-terminal pro-brain natriuretic (NT-proBNP) and troponin I peptides in emergency department patients presenting with palpitations. METHODS: Two groups of patients with palpitations but without documented supraventricular tachycardia were compared: a group with supraventricular tachycardia (n = 49) and a control group (n = 47). Both groups were diagnosed using electrophysiological studies during the study period. Blood samples were obtained from all of the patients to determine the NT-proBNP and troponin I levels within the first hour following arrival in the emergency department. RESULT: The mean NT-proBNP levels were 207.74±197.11 in supraventricular tachyarrhythmia group and 39.99±32.83 pg/mL in control group (p